2009
DOI: 10.1016/j.virol.2008.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from polyoma middle T antigen on signaling and transformation: A DNA tumor virus contribution to the war on cancer

Abstract: Middle T antigen (MT) is the principal oncogene of murine polyomavirus. Its study has led to the discovery of the roles tyrosine kinase and phosphoinositide 3-kinase (PI3K) signaling in mammalian growth control and transformation. MT is necessary for viral transformation in tissue culture cells and tumorigenesis in animals. When expressed alone as a transgene, MT causes tumors in a wide variety of tissues. It has no known catalytic activity, but rather acts by assembling cellular signal transduction molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 224 publications
0
41
0
Order By: Relevance
“…One widely used transgenic mouse model of mammary tumor formation is driven by expression of MT transcribed from the MMTV promoter (Guy et al 1992). MT is a surrogate for an activated RTK and is dependent on both the PI3K and Ras/Raf pathways for transformation (Whitman et al 1985;Ichaso and Dilworth 2001;Schaffhausen and Roberts 2009). By examining the effect of heterozygous ablation of p110a on MT-induced tumorigenesis, we found that the onset of palpable tumor formation was markedly delayed upon loss of one copy of p110a ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One widely used transgenic mouse model of mammary tumor formation is driven by expression of MT transcribed from the MMTV promoter (Guy et al 1992). MT is a surrogate for an activated RTK and is dependent on both the PI3K and Ras/Raf pathways for transformation (Whitman et al 1985;Ichaso and Dilworth 2001;Schaffhausen and Roberts 2009). By examining the effect of heterozygous ablation of p110a on MT-induced tumorigenesis, we found that the onset of palpable tumor formation was markedly delayed upon loss of one copy of p110a ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…To study the effect of ablating p110 isoforms on MT-or NeuT-associated PI3K activity, cells were starved to minimize confounding signals from the activation of other receptors. While MT binds to the p85/p110 complex directly (Schaffhausen and Roberts 2009), HER3 recruits PI3K to an activated HER2/ Neu (Supplemental Fig. 4A).…”
Section: The P110a Isoform Is Required For the Growth Of Established mentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosinephosphorylated PyVmT promotes proliferation by activating classical mitogenic signaling through the Ras-MAP kinase and PI3-kinase pathways (19,20). As SFKs phosphorylate tyrosine residues on PyVmT, loss of PyVmT tyrosine phosphorylation may explain the proliferation defect in cells lacking c-Src.…”
Section: Silencing or Deletion Of C-src Inhibits Proliferation Of Pyvmentioning
confidence: 99%
“…The mouse mammary tumor virus (MMTV)-PyMT mammary tumor system continues to be extensively employed to examine virtually every issue that is relevant to breast cancer. The reader is also referred to earlier reviews dealing with MT (84,85,121,144,251,258).…”
Section: Vol 73 2009 Role Of Pyv Mt In Signaling and Tumorigenesis 543mentioning
confidence: 99%